TANGGUNG JAWAB MALPRAKTEK MEDIS DOKTER DITINJAU DARI ASPEK HUKUM PERDATA (PENDEKATAN MEDIKO LEGAL) - Adityo Putro Prakoso Wiwiek Wibowo (Qistie Jurnal Ilmu Hukum, 2015)
Medical malpractice is a form of physician errors in their profession (professional misconduct)or forms of therapy failure in efforts to help patients, which may occur because of the elementof intent or negligence. The error can be either provide therapies that are less carefully orcareless, or has violated the code of ethics or standards operations (SOP). It is caused due tolack of skill and lack of experience, or perform medical acts outside expertise. Medicalmalpractice actions can be responsibility not only limited to the realm of medical ethics, butalso the law. Liability in civil law can be based on breach of contract, on condition that the doctor - patient has been bound in the agreement, the transaction therapeutic. The nature of this agreement in the form of "effort" to find a cure diseases doctor (effort agreement”).Whereas if on the basis of tort, the act took place outside the framework of the agreement, forexample, the doctor has violated SOP, or codes of conduct. Keywords: medical malpractice, “effort” agreement.